Sensors of vibration and acoustic emission for monitoring of boring with skiving cutters; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Shamarin N. N. Nikolay Nikolaevich; Filippov A. V. Andrey Vladimirovich; Podgornykh O. A. Oleg Anatolievich; Filippova E. O. Ekaterina Olegovna (2017, 2017)
Title screen